Birt-Hogg-Dubé Syndrome, a Rare Case in Korea Confirmed by Genetic Analysis - Shin, Won Woong (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Simple benign tumors can present as part of a syndrome with substantial mortality. Fibrofolliculomas are benign skin tumors most often associated with the Birt-Hogg-Dubé syndrome (BHDS). The most life-threatening complication of this syndrome is renal cancer and other major features include multiple lung cysts and spontaneous pneumothorax. We present the case of a 54 year-old man with multiple flesh-colored papules on his face confirmed histologically as fibrofolliculomas. He had a history of recurrent pneumothorax and chest computed tomography showed multiple lung cysts. To confirm the diagnosis of BHDS, we conducted gene analysis that revealed a single nucleotide duplication in the folliculin (FLCN) gene (Exon 11, C.1285dupC). BHDS confirmed by the FLCN gene mutation is rarely reported in Korea. Appropriate investigation is recommended whenever a patient with benign skin tumors is encountered.